Thoracoscopic Resection of Congenital Lung Malformation: Looking for the Right Preoperative Assessment - Macchini, Francesco; Borzani, Irene; Cavalli, Silvia; Morandi, Anna; D'Angelo, Ida Daniela; Zanini, Andrea; Ferrari, Carlo; Ichino, Martina; Leva, Ernesto (European Journal of Pediatric Surgery, 2019)
Introduction Consensus on the best postnatal radiological evaluation of congenital lung malformations (CLMs) is still lacking. In recent years, the interest on magnetic resonance imaging (MRI) has grown, but its role is still unknown.Aim The aim of the study was to identify the best preoperative diagnostic assessment for CLM.Materials and Methods All patients with a prenatal suspicion of CLM between January 2014 and February 2018 were studied. Asymptomatic newborns underwent MRI, during spontaneous sleep without contrast. Patients with a positive MRI were scheduled for computed tomography (CT) within the fourth month of life. Thoracoscopic resection was performed in cases with a pathological CT. MRI, CT, and surgical findings were compared based on dimension, localization, and features of the CLM using the Cohen's kappa test (K).Results A total of 20 patients were included (10 males). No difference was found in the diameter and site of the lesions always localized in the same side (K = 1) and in the same pulmonary lobe (K = 1). Infants who underwent thoracoscopic resection included: three congenital pulmonary airway malformations (CPAMs), five extralobar and eight intralobar sequestrations (bronchopulmonary sequestrations [BPSs]), three bronchogenic cysts, and one congenital emphysema. The concordance between MRI and CT and between radiological investigations and pathology was satisfactory for the greatest part of the studied variables. MRI showed sensitivity of 100%, specificity of 82%, positive predictive value of 50% and negative predictive value of 100% for CPAM and 77, 100, 100, and 80% for BPS, respectively.Conclusion MRI proved to be a reliable diagnostic investigation for CLM with high sensitivity and specificity. Early MRI in spontaneous sleep without contrast and preoperative contrast CT scan is a valuable preoperatory assessment.
Keywords: congenital lung malformations; thoracoscopy; magnetic resonance imaging; computed tomography scan